1994
DOI: 10.1080/10587259408037743
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline-State Photoisomerization and Photoinduced Phase Transition of a Cobaloxime Complex

Abstract: The ctystal of (~-cyanoethyl)bis(dimethylglyoximato)(4-methylpyridine)cobalt(III) exhibits a reversible single crystal-to-single crystal thermal phase transition at 343 K. The P-cyanoethyl group of the crystal was isomerized to a-cyanoethyl group retaining the single crystal form when the crystal was irradiated with a strong Xe lamp above 343 K, although the crystal was decomposed below the temperature. On the other hand, when the crystal was exposed to a weak Xe lamp at 340 K, the crystal showed the phase tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The molecular structure after photoirradiation revealed that only one configuration of the 1-ce group was produced, which is shown in Figure 107. The ratio of the 2-ce and 1-ce groups is 0.7 and 0.3, respectively [114].…”
Section: Crystallography Reviews 93mentioning
confidence: 99%
“…The molecular structure after photoirradiation revealed that only one configuration of the 1-ce group was produced, which is shown in Figure 107. The ratio of the 2-ce and 1-ce groups is 0.7 and 0.3, respectively [114].…”
Section: Crystallography Reviews 93mentioning
confidence: 99%
“…A system that shows cooperative phenomena such as a phase transition triggered by external light stimulation is an attractive target for materials science. Recently, it has been reported that weak photoexcitation can trigger macroscopic phase changes in several systems such as π-conjugated polymers, liquid crystals, charge transfer (CT) crystals, radical salts, and transition metal oxides. In these materials, cooperative effects in crystals, such as electron−lattice and electron−electron interactions, are considered to play a key role in the driving process of these unusual photoeffects . In other words, the localized photoexcited states and/or photocarriers induce the lattice, electronic, and magnetic structure fluctuations around them via cooperative interactions, finally triggering macroscopic phase changes.…”
Section: Introductionmentioning
confidence: 99%